PENERAPAN MODEL CONTEXTUAL TEACHING LEARNING (CTL) BERBANTUAN MEDIA LINGKARAN UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI MENUNJUKAN JENIS DAN PERSEBARAN SUMBER DAYA ALAM - Chizbullah, Yust Ibrahim; Kurnia, Dadang; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2017)
This research is based on the problem of ips learning in elementary school. The formulation of the problem as follows: how the planning, implementation, and description of the learning outcomes of the application of CTL model circled media to show the type and distribution of natural resources in SDN Randegan Wetan 1.6This application is implemented in order to improve and improve the learning process. The method used in this research is the method of PTK with research subjects of students of class IV. The research design used is the McMalm model. Taggart and istrumen used are teacher performance observation instruments, student performance observation, field notes, interview guides, and test questions sheet.2Based on the results of research conducted as much as 2 cycles, the percentage of achievement mastery increased from the initial data up to cycle 2 can be said to increase. In the initial data of student learning outcomes, the percentage of mastery reaches 35.8%, in cycle 1 the percentage of completeness reaches 64.2%, and in cycle 2 the percentage of completeness reaches 85.7%. Thus, it can be concluded that the use of the application of CTL7model of circular media on the subject shows the type and distribution of natural resources is said9to be successful.